Association between the empirical dietary inflammatory index and cardiorespiratory fitness in Tehranian adults in 2017–2018 - Payandeh, Nastaran; Shahinfar, Hossein; Babaei, Nadia; Davarzani, Samira; Ebaditabar, Mojdeh; Djafarian, Kurosh; Shab-Bidar, Sakineh (Frontiers in Nutrition, 2022)
Background: Inflammatory-related chronic diseases are increasing in our country with high consumption of a diet containing pro-inflammatory potential and a sedentary lifestyle. EDII (empirical dietary inflammatory index), was developed as a tool to assess dietary effects on systemic inflammation. We examined the hypothesis that specific dietary patterns reflecting systemic inflammation are associated with cardiorespiratory fitness (CRF) in Tehranian adults. Methods: This cross-sectional study was carried out on 270 adults’ resident of Tehran. Dietary intake was assessed using a 168-item valid and reliable food frequency questionnaire. EDII score was developed according to participant dietary intakes of 21 item pre-defined food groups. CRF was assessed by using a graded exercise treadmill test. Anthropometric measurements were assessed using standard methods. To discover the association between CRF and EDII we used multivariable logistic regression analysis. Results: Those who were in the third tertile of EDII compared to the first tertile had 57 percent lower odds of having better VO2Max (ml/kg/min) (OR: 0.43; 95% CI: 0.16, 1.12, P=0.01). There were no significant differences between tertiles of EDII score in terms of VO2 (L.min) and VO2 (LBM) before and after adjusting for confounders. There was a significant decrease in VO2Max (ml/kg/min) across tertiles of EDII after controlling for covariates (p-value=0.04). metabolic syndrome (MetS) 0.81(0.39,1.68) but the association was no significant (p=0.58). There was a significant inverse association between EDII score and VO2Max (ml/kg/min) (β=-0.35, P=0.001). Conclusions: Our finding demonstrated that higher EDII might be associated with lower CRF in Tehranian adults. Prospective studies are needed to shed light on the causal link between EDII and CRF.